The impact of Malta's free childcare scheme on female employment - Natalia Bezzina Maltseva (Central Bank of Malta, 2026)
This study evaluates the impact of Malta's 2014 childcare reform, a universal Free Childcare Scheme for children aged 3 months to 3 years, on female employment. Using a difference-in-differences (DD) framework and matched DD models, I find that the reform may have increased the probability of female employment by 1.3-2.4 percentage points, with effects growing over time. Heterogeneity analyses reveal that employment gains were disproportionately concentrated among single mothers and mothers with multiple children, i.e., subgroups that have historically faced greater structural barriers to employment. Notably, the reform likely helped reduce pre-existing employment gaps by up to 26% for single mothers, 39.3% for two-child mothers and 14.1% for mothers with three or more children. However, no persistent employment effects were observed post-eligibility, and fiscal savings were limited to reduced welfare claims among single parents. These findings contribute to the global literature on childcare subsidies by highlighting how nation-wide access, when subject to well-designed eligibility criteria, can narrow labour market disparities, while also showing that persistent employment effects require sustained support beyond the early childhood years.
Keywords: J13; J22; I38; H31; C21; 330; Childcare subsidies; Female employment; Difference-in-Differences; Universal Childcare